STRESS MARKERS AND BIOCHEMICAL ALTERATIONS DUE TO CAMINUM NANOPARTICLES EXPOSURE IN FISH Cirrhinus mrigala - UMAMAHESWARI, M.; KRISHNAMURTHY, R.; ELUMALAI, K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
The present investigation carried out to determine the effect of cadmium Nano Particles (Cd NPs) on stress bio-markers assay in Cirrhinus mrigala (C. mrigala) fish fingerlings. The nanoparticles (NP) in fishes carried through the use of ion transporters or by endocytosis. Aquatic metal exposure may cause the deleterious effects to all aquatic organisms. The previous studies have shown that the NP were found to deposit in the liver of fishes. The C. mrigala fish fingerlings were acclimatized to laboratory conditions for 10days at a water temperature of 27 ± 2°C, before starting the experiment. They were fed ad libitum regular fish feed two times a day in the morning and evening. Bio-assays were carried out for 10 days. It was revealed that the LC50 value of Cd NP as 50 ppm in C. mrigala. A series of five different concentrations such as 20, 40, 60, 80,100 ppm of CdNP suspension with 100 nm in size was mixed intra peritoneally per kg of fish weight. The biochemical enzyme studies (i.e.) alkaline phosphatase, Lactate dehydrogenase (LDH) and Malate dehydrogenase (MDH) were estimated by standard procedures in tissues such as liver, and kidney. However, enzymes LDH and MDH showed the biochemical changes during the stress condition in the fish on nanoparticles exposure. The outcome result data were tabulated and statistically analyzed by Statistical Package for the Social Sciences version 16 (SPSS), one-way ANOVA (Analysis of Variance) used to observe the treatment effect. The present study reveals that the MDH enzyme level in the 2nd and 10th day in liver and kidney were 0.54±0.60; 0.9±0.15 and 0.24± 0.48; 0.41± 0.07 respectively. On 10th day the alkaline phosphatase intensity in the liver and kidney were 10.45± 03 and 10.24± 0.80 respectively.